Characteristics of diabetic patients hospitalized in two Hospitals of EsSalud Piura - Espinoza-Morales, Frank (2015)
Objective: To describe the frequency of patients with diabetes mellitus type 2 hospitalized in Piura. Material and Methods: we conducted a cross-sectional study in two hospitals of greater complexity care of EsSalud in Piura: Hospital III Jose Cayetano Heredia and Hospital II Jorge Reategui Delgado. Results: We obtained the clinical-demographic characteristics of the participants during the International Diabetes Day 2014. Of the 183 in patients in both centers, 39 patients (21%) had diabetes mellitus type 2; the mean age was 67.8 ± 11.8. The medical records do not report hospital admission blood glucose and blood glucose during hospitalization in 17 and 24 participants, respectively. The medical records do not report weight of 31 participants. Diabetic foot was the primary cause of hospitalization. Conclusion: We conclude that diabetes mellitus type 2 is common in hospitalized patients of Essalud Piura, there is no proper record in the medical records of parameters such as weight and glycemic control.